Effect of jeevamrut on productivity and profitability of wheat under organic farming - BHADU, KARAN; SHARMA, S K; CHOUDHARY, ROSHAN; YADAV, S K; JAIN, R K; JAT, GAJANAND; RAVISHANKER, N (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during rabi 2017-18 and 2018-19 at organic farming unit of Instructional Agronomy Farm, Rajasthan College of Agriculture, Udaipur, Rajasthan to study the influence of different concentrations of jeevamrut and its time of application on growth, yield attributes and yield of wheat grown under organic farming. Results revealed that a significant increase in plant height, dry matter accumulation, number of effective tillers, number of spikelets/ear, number of grains/ear, ear length and grain weight/ear, was observed with the application of 10% jeevamrut over control, 4% jeevamrut and 6% jeevamrut. There was no significant difference observed in grain and straw yield of wheat with the application of 4% and 6% jeevamrut over control. However, application of 8% and 10% jeevamrut significantly increased the grain and straw yield of wheat over control. Application of jeevamrut at 60 and 75 DAS significantly increased plant height, dry matter accumulation, number of effective tillers, number of spikelets/ear, number of grains/ear, ear length and grain weight/ear over the application of jeevamrut at 75 and 90 DAS. Application of jeevamrut twice at 60 and 75 DAS and 75 and 90 DAS significantly increased the grain and straw yield of wheat as compared to one time application of jeevamrut 75 and 90 DAS alone. There was no significant interaction found in the concentration of jeevamrut and its time of application.